Mediation role of brand trust on the impact of e-wom perception on purchase intention of ms glow products on shopee study in kelurahan Tomuan Pematangsiantar - Liharman Saragih; Siti Rohani; Theresia Febriana Tampubolon; Wirda Yuliani; Tri Mutiara Sakinah (Institute of Computer Science (IOCS), 2023)
The main objective of this research is to examine the effect of electronic word-of-mouth (eWOM) perceptions on purchase intention; Consider brand trust as a mediating variable. This study takes a customer perspective; Known Tomua villagers who have an active account on SHOPEE. The conceptual framework of this study was tested using data collected from a questionnaire addressed to a sample of 123 respondents in Tomuan. Statistical results of validity tests, multicollinearity tests, results of multiple linear analysis, results of the T test (partial), results of the F test and results of the deterministic test show that the reliability of eWOM and the quality of eWOM have a significant and positive effect on purchase intention. Regarding the mediating role of brand trust, the results show that brand trust mediates the relationship between the independent and dependent variables. Therefore, research results, recommendations and future research are also discussed.